Effects of propofol on macrophage activation and function in diseases - Yi, Shuyuan; Tao, Xinyi; Wang, Yin; Cao, Qianqian; Zhou, Zhixia; Wang, Shoushi (Frontiers in Pharmacology, 2022)
Macrophages work with monocytes and dendritic cells to form a monocyte immune system, which constitutes a powerful cornerstone of the immune system with their powerful antigen presentation and phagocytosis. Macrophages play an essential role in infection, inflammation, tumors and other pathological conditions, but these cells also have non-immune functions, such as regulating lipid metabolism and maintaining homeostasis. Propofol is a commonly used intravenous anesthetic in the clinic. Propofol has sedative, hypnotic, anti-inflammatory and anti-oxidation effects, and it participates in the body's immunity. The regulation of propofol on immune cells, especially macrophages, has a profound effect on the occurrence and development of human diseases. We summarized the effects of propofol on macrophage migration, recruitment, differentiation, polarization, and pyroptosis, and the regulation of these propofol-regulated macrophage functions in inflammation, infection, tumor, and organ reperfusion injury. The influence of propofol on pathology and prognosis via macrophage regulation is also discussed. A better understanding of the effects of propofol on macrophage activation and function in human diseases will provide a new strategy for the application of clinical narcotic drugs and the treatment of diseases.